2006
DOI: 10.1186/1471-213x-6-21
|View full text |Cite
|
Sign up to set email alerts
|

Functional conservation of Pax6 regulatory elements in humans and mice demonstrated with a novel transgenic reporter mouse

Abstract: Background: The Pax6 transcription factor is expressed during development in the eyes and in specific CNS regions, where it is essential for normal cell proliferation and differentiation. Mice lacking one or both copies of the Pax6 gene model closely humans with loss-of-function mutations in the PAX6 locus. The sequence of the Pax6/PAX6 protein is identical in mice and humans and previous studies have shown structural conservation of the gene's regulatory regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…We found that tau-GFP reporter expression in the forebrain and eye of two transgenic lines (DTy54 and Y223) carrying full-length reporter YAC transgenes derived from Y593 largely resembled that of Pax6, in agreement with previous studies [30,38]. However, close examination of tau-GFP and endogenous Pax6 expression at the cellular level highlighted some interesting differences.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found that tau-GFP reporter expression in the forebrain and eye of two transgenic lines (DTy54 and Y223) carrying full-length reporter YAC transgenes derived from Y593 largely resembled that of Pax6, in agreement with previous studies [30,38]. However, close examination of tau-GFP and endogenous Pax6 expression at the cellular level highlighted some interesting differences.…”
Section: Discussionsupporting
confidence: 90%
“…DTy54 transgenic mice carry a single copy of YAC 1123, which is a full-length version of YAC 593 modified so that it expresses tau-tagged GFP instead of PAX6 (summarized in the upper part of Figure 1B) [38]. To compare expression of the tau-GFP reporter and endogenous Pax6, coronal sections along the rostral–caudal axis were double-immunolabeled for tau-GFP and Pax6 protein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations